Peran Teknologi dalam Transformasi Digital: Tantangan dan Peluang untuk Organisasi dan Bisnis - Pratama, Intan Elfina; Putri, Tiffany Melia (CV. ITTC INDONESIA, 2025)
The digital era has brought significant changes to how organizations operate, interact, and innovate. Organizations face various challenges, including rapid technological advancements, the need for fast and adaptive digital transformation, swift market shifts, evolving consumer behavior, and increasingly intense competition. However, behind these challenges lie substantial opportunities such as leveraging data, automating processes, and expanding market reach through online platforms. Organizations can also use data to make more accurate decisions, collaborate with digital partners, and build closer relationships with customers through personalized services. Using literature review and a qualitative descriptive approach, this study explores how organizations can design responsive and sustainable strategies in the midst of digital dynamics. The findings indicate that organizations capable of integrating digital technologies with a clear business vision have a greater potential to survive and grow in the digital era. Therefore, organizations need flexible and innovative strategies that focus on developing digital capabilities and managing change effectively.